DETERMINATION OF THE COMPETITIVENESS IN THE MEXICAN AGRICULTURAL SECTOR, 1980-2009 - Ayala Garay, Alma Velia; Sangerman-Jarquín, Dora Ma.; Schwentesius Rindermann, Rita; Almaguer Vargas, Gustavo; Jolalpa Barrera, José Luis (Revista Mexicana de Ciencias Agrícolas, 2018)
The agricultural sector in Mexico is becoming less competitive, since there is a growing food import, which implies the existence of reduced ability to produce and distribute them in the market. The aim of this paper was to analyze macroeconomic indicators to quantify the competitiveness of agriculture in Mexico and its tendency, within a framework of trade liberalization. The revealed additive competitiveness was less than zero, with a decreasing trend. At the same time, food self-suff iciency, balance of trade, gross domestic product of agriculture (GDPA) in relation to GDP, per capita nominal GDPA and productivity wages, showed a signif icant tendency to decrease, so that, macroeconomic fundamentals will not be an appropriate pillar to improve agricultural competitiveness in the analyzed context. Trade liberalization has not resulted in increased competitiveness, but it can be improved by giving priority to food sovereignty by strengthening its domestic market and investing in public goods.
Keywords: competitiveness; macroeconomic variables; trade liberalization